Gurule proclaims 'Southwell Day' (Raton, New Mexico Raton Range, 1974)
Newspaper Article on the City Commission Declaring August 26, 1974 John Southwell Day.
Master list item #: 33
File location is in the Raton File Cabinet
Keywords: Southwell, John; Gurule, Robert E; Sprouje, Eva Mae; City Commission; Local History; Biography; Life and Customs; Senior Residents; Honoring; acknowledgement; Raton, New Mexico